STUDENT CRITICISM TO JOKOWI'S POLICY : (Critical Discourse Analysis on Uploads of BEM UI 2021 on Instagram) - najamuddin; Hafied Cangara; Muliadi Mau (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
This study aims to analyze critical text messages of BEM UI 2021 students on Instagram social media. The primary data in this study is the upload of the @bemui¬_official account entitled the king of lip service. This research uses the analysis method of Teun A Vand Dijk. The results of this study found that the discourse of the king of lip service was a student criticism movement for Jokowi's policies that were not realized. The nickname is a form of criticism of Jokowi's promise about. First, Jokowi's statement to long for demonstrations, but various demonstrations actually get repression. Second, Jokowi wants to revise the ITE Law, but it has resulted in the proposal of a new article. Third, Jokowi wants to strengthen the KPK which actually ends in indications of weakness. Fourth, Jokowi allowed the Omnibus Law to be sued at the Constitutional Court (MK), but contradicted Airlangga Hartarto's statement to the Constitutional Court to reject all claims against the Job Creation Law. Meanwhile, the use of social media Instagram in the student criticism movement is an alternative means to fight the discourse from the government and mobilize the student movement. Another finding is the reason why students criticize the government. First, students have a special identity, so from that identity there is a moral burden to criticize the government. Second, students have anxiety about their uncertain future. Finally, they expressed their anxiety through criticism on social media and street demonstrations, in the hope that social change would occur. Third, students have the burden of history that was obtained from the previous generation of students.